Afatinib-based combination regimens for the treatment of solid tumors: rationale, emerging strategies and recent progress. (February 2016) - Bennouna, Jaafar; Moreno Vera, Shanti Ricardo
In oncology, there is a clinical need for novel combination therapy regimens that maximize efficacy and delay resistance to individual treatment modalities. Given the role of aberrant ErbB receptor signaling in the pathogenesis of many human cancers, there is rationale for incorporating afatinib, an irreversible pan-ErbB tyrosine kinase inhibitor, into such combinations. This review focuses on: pharmacological properties of afatinib that facilitate its use in combination; preclinical rationale for the combination of afatinib with other agents; and recently completed, and ongoing, clinical trials of afatinib-based combinations across tumor types. Based on these data, we emphasize a number of areas of high unmet medical need that could benefit from afatinib-based combinations, including patients with relapsed/refractory non-small-cell lung cancer.